Comparison of Effectiveness of Two Polyethylene Covers on Body Temperature and Oxygen Saturation of Neonates Transferring to NICUs - Naiire Salmani; Zahra Dehghan; Zahra Mandegari; Azita Aryaee; Shima Dehghan (Mashhad University of Medical Sciences, 2019)
Background: The sudden exposure of premature newborns to a cold and dry environment can lead to hypothermia. This study aimed at comparing the effectiveness of two polyethylene covers on the body temperature and oxygen saturation of premature neonates. Methods: This experimental study was conducted on 72 premature newborns in the neonatal intensive care unit (NICU) of Shahid Sadoughi Hospital in Yazd, Iran. The study subjects were randomly assigned into three groups, including the neonates with polyethylene head cap, polyethylene body bag, and routine care. The data were collected using a thermometer and a pulse oximeter. The data analysis was performed through descriptive statistics, Chi-square test, analysis of variance (ANOVA), repeated measures ANOVA, and Tukey test using SPSS (version 18) software. Results: There was a significant difference in the mean body temperature of control and intervention groups immediately after their NICU admission and 1 h later. Other significant differences were found in the mean of oxygen saturation belonging to the control group and the hat group upon admission and 1 h later. Also, the mean scores of oxygen saturation belonging to the control group were compared with those of the bag group, and the differences were significantly different 1 h after the admission. Conclusion: In the light of these findings, the application of both polyethylene head cap and body bag can maintain the body temperature and oxygen saturation in the premature neonates transferring to the NICU. In particular, the head cap seems to better improve than oxygen saturation.